2014
DOI: 10.1136/bcr-2014-204364
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of uterine leiomyoma during labour

Abstract: Uterine rupture in labour requires an emergency caesarean section. In women with a uterine scar, either from gynaecological surgery or from a previous caesarean section, it is well documented that the risk of rupture is higher than in those without. Spontaneous uterine rupture in a uterus with fibroids during pregnancy or labour is extremely rare. We present a case of a 33-year-old, unbooked pregnant woman from Nigeria who had a uterine rupture secondary to fibroids. She required an emergency caesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Similarly, there are also reports of spontaneous rupture of fibroid intrapartum and in the early second trimester at 15 and 20 weeks gestation [11,12,15]. To date, there is no report of a pregnant woman with known fibroids and no history of myomectomy presenting with spontaneous rupture of fibroid in the third trimester prior to the onset of labor, as we present here.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, there are also reports of spontaneous rupture of fibroid intrapartum and in the early second trimester at 15 and 20 weeks gestation [11,12,15]. To date, there is no report of a pregnant woman with known fibroids and no history of myomectomy presenting with spontaneous rupture of fibroid in the third trimester prior to the onset of labor, as we present here.…”
Section: Discussionsupporting
confidence: 70%
“…This case highlighted the following two findings: First, leiomyomas can rupture during pregnancy. There have been cases reported of the rupture of a blood vessel overlying the leiomyoma during pregnancy 5,6 and after labor, 7 resulting in intra‐abdominal bleeding; a case of nonreassuring fetal status and intra‐abdominal bleeding due to the rupture of a leiomyoma during labor has also been reported 4 . Thus, the rupture of a leiomyoma can occur at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Ramskill et al reported the rupture of a uterine fibroid during labor in a 33‐year‐old patient. Another case reported a spontaneous uterine bleed at 15 weeks of gestation from a fibroid.…”
Section: Discussionmentioning
confidence: 99%